Entrepreneurial Intention on iGeneration: A Survey on Students of Economy Education in Pekanbaru City - Wardani Purnama Sari; Khairunnisa Khairunnisa; Jean Elikal Marna (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
This article reveals Entrepreneurial Intention in igeneration. In this paper, entrepreneurial attitude is an intervening variable between entrepreneurial education and relational support towards entrepreneurial intention. The survey method used in the research uses Amos-based SEM (structural Equation Modeling). Economic education students in Pekanbaru were a sample of 276 people. The results of this research reveal that entrepreneurial attitude is a variable that can strengthen the influence of entrepreneurship education and relational support on entrepreneurial intention. So these variables have a significant influence on students' entrepreneurial intention.